2007
DOI: 10.1007/s00299-006-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tolerance to oxidative stress in transgenic tobacco plants expressing three antioxidant enzymes in chloroplasts

Abstract: The effect of simultaneous expression of genes encoding three antioxidant enzymes, copper zinc superoxide dismutase (CuZnSOD, EC 1.15.1.1), ascorbate peroxidase (APX, EC 1.11.1.11), and dehydroascorbate (DHA) reductase (DHAR, EC 1.8.5.1), in the chloroplasts of tobacco plants was investigated under oxidative stress conditions. In previous studies, transgenic tobacco plants expressing both CuZnSOD and APX in chloroplast (CA plants), or DHAR in chloroplast showed enhanced tolerance to oxidative stresses, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(122 citation statements)
references
References 29 publications
(37 reference statements)
7
113
0
2
Order By: Relevance
“…2c in their paper) which clearly shows elevated activity of all the SOD isoenzyme activities except one, in their transgenic plants. Lee et al (2007b), reporting on plants simultaneously expressing 2 or 3 ROS scavenging enzymes (including SOD) published an activity gel where there is clear enhancement of an unidentified native SOD (possibly FeSOD on the basis of its proximity to the engineered Cu/Zn enzyme). Curiously the authors of neither paper allude to this interesting finding which, together with our results, suggests redox-mediated retrograde signalling between the chloroplasts and the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2c in their paper) which clearly shows elevated activity of all the SOD isoenzyme activities except one, in their transgenic plants. Lee et al (2007b), reporting on plants simultaneously expressing 2 or 3 ROS scavenging enzymes (including SOD) published an activity gel where there is clear enhancement of an unidentified native SOD (possibly FeSOD on the basis of its proximity to the engineered Cu/Zn enzyme). Curiously the authors of neither paper allude to this interesting finding which, together with our results, suggests redox-mediated retrograde signalling between the chloroplasts and the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SOD and APX have proven an effective combination in transgenic tobacco (Kwon et al 2002;Kim et al 2005), potato (Tang et al 2006) and tall fescue (Lee et al 2007a). In one study with tobacco (Lee et al 2007b) three components of the ROS defence network (SOD, APX and DHAR) were shown to provide further improvements in tolerance to salinity and MV, in comparison with plants over-expressing only the first two of these.…”
Section: Introductionmentioning
confidence: 99%
“…Also, transgenic tobacco or potato that simultaneously overexpress a SOD and an APX gene show enhanced tolerance to necrosis caused by the herbicide paraquat in comparison to transgenic plants that overexpress either SOD or APX (Kwon et al, 2002;Tang et al, 2006). Moreover, simultaneous overexpression of SOD, APX and DHAR in chloroplasts is more effective in inducing tolerance to paraquat and salt treatments, as compared with single or double transformants (Lee et al, 2007). In the present study, DHAR activity was considerably higher at 30 u C, as compared with 20 u C, in both mock-inoculated and TMVinfected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include plants overexpressing different antioxidant enzymes, such as chloroplast superoxide dismutase (Sen Gupta et al 1993), peroxisomal ascorbate peroxidase (Wang et al, 1999), or these two enzymes together with dehydroascorbate reductase (Lee et al 2007). Tolerance against UV-B radiation was also increased in tobacco leaves, where reactive oxygen scavenging capacity was enhanced by preceding mild drought (Hideg et al, 2003, Kubis andRybus-Zajac, 2008).…”
Section: Introductionmentioning
confidence: 99%